The T allele of a single-nucleotide polymorphism 13.9 kb upstream of the lactase gene (LCT) (C-13.9kbT) does not predict or cause the lactase-persistence phenotype in Africans. - Mulcare, C; Weale, M; Jones, A; Connell, B; Zeitlyn, D; Tarekegn, A; Swallow, D; Bradman, N; Thomas, MG (Cell Press, 2004)
The ability to digest the milk sugar lactose as an adult (lactase persistence) is a variable genetic trait in human populations. The lactase-persistence phenotype is found at low frequencies in the majority of populations in sub-Saharan Africa that have been tested, but, in some populations, particularly pastoral groups, it is significantly more frequent. Recently, a CT polymorphism located 13.9 kb upstream of exon 1 of the lactase gene (LCT) was shown in a Finnish population to be closely associated with the lactase-persistence phenotype (Enattah et al. 2002). We typed this polymorphism in 1,671 individuals from 20 distinct cultural groups in seven African countries. It was possible to match seven of the groups tested with groups from the literature for whom phenotypic information is available. In five of these groups, the published frequencies of lactase persistence are >/=25%. We found the T allele to be so rare that it cannot explain the frequency of the lactase-persistence phenotype throughout Africa. By use of a statistical procedure to take phenotyping and sampling errors into account, the T-allele frequency was shown to be significantly different from that predicted in five of the African groups. Only the Fulbe and Hausa from Cameroon possessed the T allele at a level consistent with phenotypic observations (as well as an Irish sample used for comparison). We conclude that the C-13.9kbT polymorphism is not a predictor of lactase persistence in sub-Saharan Africans. We also present Y-chromosome data that are consistent with previously reported evidence for a back-migration event into Cameroon, and we comment on the implications for the introgression of the -13.9kb*T allele.